Inhibition of IL-1 Signaling by Antisense Oligonucleotide-mediated Exon Skipping of IL-1 Receptor Accessory Protein (IL-1RAcP) - A Seda Yılmaz-Eliş; Annemieke Aartsma-Rus; Peter AC 't Hoen; Huma Safdar; Cor Breukel; Bart JM van Vlijmen; Judith van Deutekom; Sjef de Kimpe; Gert-Jan van Ommen; J Sjef Verbeek (Molecular Therapy: Nucleic Acids, 2013)
The cytokine interleukin 1(IL-1) initiates a wide range of proinflammatory cascades and its inhibition has been shown to decrease inflammation in a variety of diseases. IL-1 receptor accessory protein (IL-1RAcP) is an indispensible part of the IL-1R complex that stabilizes IL-1/IL-1R interaction and plays an important role in the signal transduction of the receptor complex. The soluble form of IL-1RAcP (sIL-1RAcP) contains only the extracellular domain and serves as a natural inhibitor of IL-1 signaling. Therefore, increasing sIL-1RAcP levels might be an attractive therapeutic strategy to inhibit IL-1–driven inflammation. To achieve this we designed specific antisense oligonucleotides (AON), to redirect pre-mRNA IL-1RAcP splicing by skipping of the transmembrane domain encoding exon 9. This would give rise to a novel Δ9IL-1RAcP mRNA encoding a soluble, secreted form of IL-1RAcP, which might have similar activity as natural sIL-1RAcP. AON treatment resulted in exon 9 skipping both in vitro and in vivo. A single dose injection of 10 mg AON/kg body weight induced 90% skipping in mouse liver during at least 5 days. The truncated mRNA encoded for a secreted, soluble Δ9IL-1RAcP protein. IL-1RAcP skipping resulted in a substantial inhibition of IL-1 signaling in vitro. These results indicate that skipping of the transmembrane encoding exon 9 of IL-1RAcP using specific AONs might be a promising therapeutic strategy in a variety of chronic inflammatory diseases.